Pewarisan Budaya Organisasi Dalam Konteks Komunikasi Organisasi (Studi Kasus Pewarisan Budaya Organisasi di Ma'soem Group Bandung) - Agustin Rozalena (KOM & REALITAS SOSIAL, 2011)
This research aim to knowing the pattern of the inheritance of the organization culture Ma'soem Group, especially in PT Ma'soem that manag the product Pertamina, and Yayasan Pendidikan Al Ma'soem, that is involve in formal education. This research method is qualitative with the case study plan. The field data is receiv from the informant, technically the data collection that is us that is the interview, observation, as well as the analysis of the document of non participation.Results of field work show that (1) the orientation and the manifestation from spiritual values and philosophy Sundanism in the organization culture Ma'soem Group is clarify  in the point of view and the mission, business strategy, structure and work procedure, system and the rule, the name, the form, and the symbol, the anecdote, the creed, and organization jargon, as well as ritual.(2) Ma'soem Group had the typical organization culture, strong, and be proud of. In this case, the values of the culture that is invest by the leader can increase the will, loyalty, and pride as well as more far creat the effectiveness of the work. The orientation of the values that are apply this including the value of the achievement that honesty, discipline, and the characteristics is believed. (3) The involvement of the leader is very big is cause by the hero factor that is strong from the founder and the first generation of the founding continuer of the organization. (4) Through the pattern of vertical communication with the communication channel in the spreading of the centipede through the story, ritual, and the rule is not written and written show that the organization Ma'soem Group is the organization that is open with input, criticism, new ideas, as well as the spirit in developing the similarity of the perception work as religious duties.(5) The inheritance of the organization culture Ma'soem Group is begun from the founder and the leader is dropp off to the managements ranks and the manager through the communication channel interpersonal, the group, and the public. Both formal and informal media.